Extended-Duration Low-Intensity Apixaban to Prevent Recurrence in Patients with Provoked Venous Thromboembolism and Enduring Risk Factors: Rationale and Design of the HI-PRO Trial - Bikdeli, Behnood; Hogan, Heather; Morrison, Ruth B.; Fanikos, John; Campia, Umberto; Barns, Briana M.; Pfeferman, Mariana B.; Snyder, Julia E.; Khairani, Candrika D.; Goldhaber, Samuel Z.; Piazza, Gregory (Thrombosis and Haemostasis, 2021)
Patients with acute venous thromboembolism (VTE) in the setting of transient provoking factors are typically treated with short-term anticoagulation. However, the risk of recurrence may be increased in the presence of enduring risk factors. In such patients, the optimal duration of treatment remains uncertain. HI-PRO is a single-center, double-blind randomized trial. Patients with deep vein thrombosis (DVT) or pulmonary embolism (PE) following a major provoking factor, including major surgery or major trauma, who completed at least 3 months of standard-dose therapeutic anticoagulation and have at least one enduring risk factor (such as obesity or heart failure) will be considered for inclusion. Patients will be randomized to apixaban 2.5 mg twice daily or placebo for 12 months. The primary efficacy outcome will be symptomatic recurrent VTE—a composite of DVT and/or PE at 12 months after randomization. Secondary efficacy outcomes include a composite of death due to cardiovascular causes, nonfatal myocardial infarction, stroke or systemic embolism, major adverse limb events, or coronary or peripheral ischemia requiring revascularization at 12 months, and individual components of these outcomes. The primary safety outcome is major bleeding according to the International Society on Thrombosis and Haemostasis definition. The study plans to enroll 600 patients (300 per arm) to have 80% power for detecting a 75% relative risk reduction in the primary outcome. Active recruitment began in March 2021. HI-PRO will provide clinically meaningful data on whether patients with provoked VTE and enduring risk factors have fewer adverse clinical outcomes if prescribed low-intensity extended-duration anticoagulation.
Keywords: venous thromboembolism; anticoagulation; apixaban; provoked